To love or not to love, that is the question: Examining the intersection of love, care, and education. (September 2021) - Shin, Minsun
This colloquium discusses the intersection of love, care, and education in the field of early childhood education and care. While the name of the field reflects the belief that both care and education are seen as legitimate elements of the field's professional discourse, love is still unspoken, undefined, and taken for granted. The author argues that love is professional yet very personal, involving the feelings and strong emotional connection that exist in a complex relationship in professional early childhood classrooms. This colloquium urges us to realize and legitimatize both love and care in the field of early childhood education and care, rather than conflating love and care.